The Prevalence of Lipoprotein(a) Measurement and Degree of Elevation Among 2710 Patients With Calcific Aortic Valve Stenosis in an Academic Echocardiography Laboratory Setting. (October 2017) - Wilkinson, Michael J.; Ma, Gary S.; Yeang, Calvin; Ang, Lawrence; Strachan, Monet; DeMaria, Anthony N.; Tsimikas, Sotirios; Cotter, Bruno
Lipoprotein(a; Lp[a]) and its associated oxidized phospholipids are causal, genetic risk factors for calcific aortic valve stenosis (CAVS). We determined the prevalence of Lp(a) measurement among 2710 patients with CAVS and 1369 control patients (∼50% of study group) without CAVS with an echocardiogram between January 2010 and February 2016 in an academic echocardiography laboratory. Lipoprotein(a) measurements were performed at a referral laboratory using an isoform-independent assay. The prevalence of any Lp(a) measurement was 4.6% (124 of the 2710) in patients with CAVS and 3.1% (42 of the 1369) in the control group ( P = .021). In patients with CAVS, mean (standard deviation) Lp(a) levels were 38 (54) mg/dL and median (interquartile range) Lp(a) levels were 14 (6-48) mg/dL. Of the 124 patients with CAVS having Lp(a) measurements, 83 (66.9%) had Lp(a) <30 mg/dL and 41 (33.1%) had Lp(a) ≥30 mg/dL. This study reflects low physician testing of Lp(a) levels in CAVS. Given the role of Lp(a) as a causal risk factor for CAVS, and the ongoing development of therapies to normalize Lp(a) levels, our results suggest that Lp(a) measurements in CAVS should be more widely obtained in clinical practice.